1991
DOI: 10.1021/bi00222a004
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin analogs of 2',5'-oligoadenylate inhibit human immunodeficiency virus infection via inhibition of reverse transcriptase

Abstract: Analogues of 2',5'-oligoadenylates (2-5A), the cordycepin (3'-deoxyadenosine) core trimer (Co3) and its 5'-monophosphate derivative (pCo3), were shown to display pronounced anti-human immunodeficiency virus type 1 (HIV-1) activity in vitro. Treatment of HIV-1 infected H9 cells with 1 microM Co3 or pCo3 resulted in an almost 100% inhibition of virus production. The compounds were encapsulated in liposomes targeted by antibodies specific for the T-cell receptor molecule CD3. Substitution of one or two cordycepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(54 citation statements)
references
References 44 publications
(68 reference statements)
2
49
0
3
Order By: Relevance
“…Cordycepin (3-deoxyadenosine, 3'-dA) is the main active ingredient. Early studies have shown that cordycepin has various biological activities, which include inhibiting inflammation (Kim et al, 2006), inhibiting platelet aggregation (Cho et al, 2007), strengthening the immune system (Zhou et al, 2008), inhibiting the polyadenylation of mRNA (Lallas et al, 2004), and inhibiting human immunodeficiency virus infection (Müller et al, 1991). Studies also have shown that cordycepin has significant anti-tumor effects such as inhibiting cell proliferation and metastasis (Nakamura et al, 2005;Chang et al, 2008;Shi et al, 2008), inducing apoptosis (Wehbe-Janek et al, 2007;Wu et al, 2007;Thomadaki et al, 2008), and interfering with cell signaling pathways (Lee et al, 2009;Wong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cordycepin (3-deoxyadenosine, 3'-dA) is the main active ingredient. Early studies have shown that cordycepin has various biological activities, which include inhibiting inflammation (Kim et al, 2006), inhibiting platelet aggregation (Cho et al, 2007), strengthening the immune system (Zhou et al, 2008), inhibiting the polyadenylation of mRNA (Lallas et al, 2004), and inhibiting human immunodeficiency virus infection (Müller et al, 1991). Studies also have shown that cordycepin has significant anti-tumor effects such as inhibiting cell proliferation and metastasis (Nakamura et al, 2005;Chang et al, 2008;Shi et al, 2008), inducing apoptosis (Wehbe-Janek et al, 2007;Wu et al, 2007;Thomadaki et al, 2008), and interfering with cell signaling pathways (Lee et al, 2009;Wong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…8 Submerged cultivated C. militaris is found to secrete cordycepin into the environment. 20 Cordycepin is found to possess antitumor activity, 21 inhibition of nuclear RNA synthesis in nerve and glial cells, 22 and antiviral activity towards HIV-1 in vitro, 23 as well as antiprotozoal effect 24 and insecticidal activity against Plutella xylostella (L.). 25 Structure-growth inhibition relationships in intestinal organisms have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…This activity has been well described in vitro with purified RNA polymerases and poly(A) polymerases from a number of organisms, including yeasts and mammals (9,10). Cordycepin has anticancer activities including induction of apoptosis, DNA double-strand break activity, and cell cycle arrest in cancer cells (11)(12)(13)(14)(15).…”
Section: Cordycepin Increases Sensitivity Of Hep3b Human Hepatocellulmentioning
confidence: 99%